THE INTELLIGENT SYSTEM FOR AUTOMOTIVE FUELS QUALITY DEFINITION - Drevetskiy , Volodymyr; Klepach, Marko (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
An intelligent system, based on hydrodynamic method and artificial neural networks usage for automotive fuels quality definition have been developed. Artificial neural networks optimal structures for the octane number of gasoline, cetane number, cetane index of diesel fuel definition have been substantiated and their accuracy has been analyzed. The implementation of artificial neural networks by means of microcontroller-based systems has been considered.